KEPASTIAN HUKUM TERHADAP HAK WARIS ANAK TIRI (STUDI TENTANG KEDUDUKAN HAK WARIS ANAK TIRI DALAM MASYARAKAT ADAT BATAK TOBA DI DESA SIGALINGGING KECAMATAN PARBULUAN) - Ade P Banjarnahor; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a country that is rich in indigenous peoples, which are owned by different regions and ethnic groups. Although the basis and characteristics are one, the customs that exist in Indonesia are very diverse and do not die in time, but are always moving and there is an obligation to always develop in accordance with the circumstances of the times and the current civilization.This study uses sociological research with data sources through interviews, especially people who are authorized, know and are related to existing problems and literature study. This research discusses the legal certainty of the inheritance rights of tiri anatomy in the Toba Batak’s ethnic.The conclusion of this study is that the position of a man in the Batak Toba’s ethnic is highly respected even though he is a stepson or a child from a previous marriage who enters the marriage of a new mother or father who is legitimate and recognized in the community and environment. exist and have full rights to the inheritance left behindKeywords: Inheritance rights, Stepchildren, Batak Toba